2012
DOI: 10.4049/jimmunol.1201183
|View full text |Cite
|
Sign up to set email alerts
|

Immunoproteasome Subunit LMP7 Deficiency and Inhibition Suppresses Th1 and Th17 but Enhances Regulatory T Cell Differentiation

Abstract: The immunoproteasome generates peptides presented on MHC class I molecules to cytotoxic T cells. ONX 0914 (formerly called PR-957) is a selective inhibitor of the immunoproteasome subunit low molecular mass polypeptide (LMP) 7 (β5i) that attenuates disease progression in mouse models of diabetes, colitis, and arthritis. The aim of this study was to investigate the effect of LMP7-specific inhibition on major Th cell differentiation pathways involved in the progression of autoimmune diseases in vitro and in vivo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
166
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 132 publications
(177 citation statements)
references
References 48 publications
9
166
2
Order By: Relevance
“…Moreover, recent studies in lymphocytes have shown that proteasome activity can also influence their differentiation and function (22)(23)(24)(25)(26). These findings, along with the observation of asymmetric proteasome During an immune response, CD8 + T lymphocytes can undergo asymmetric division, giving rise to daughter cells that exhibit distinct tendencies to adopt terminal effector and memory cell fates.…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Moreover, recent studies in lymphocytes have shown that proteasome activity can also influence their differentiation and function (22)(23)(24)(25)(26). These findings, along with the observation of asymmetric proteasome During an immune response, CD8 + T lymphocytes can undergo asymmetric division, giving rise to daughter cells that exhibit distinct tendencies to adopt terminal effector and memory cell fates.…”
Section: Introductionmentioning
confidence: 67%
“…Stability of the transcription factor Foxp3 has been shown to undergo ubiquitinproteasome system-mediated (UPS-mediated) regulation (53,54). Moreover, proteasome inhibition through genetic or pharmacologic approaches can attenuate experimental models of autoimmune disease by virtue of effects on antigen processing and presentation or direct effects on T lymphocytes (22)(23)(24). In another study, treatment of virally infected mice with the proteasome inhibitor bortezomib resulted in an impaired CD8 + T cell response, but these effects were attributed to effects on antigen presentation due to systemic administration of the drug (55).…”
Section: Proteasome Activity Influences Transcriptomic and Proteomic mentioning
confidence: 99%
“…The inhibitor ONX0914 (formerly named PR-957) irreversibly blocks the activity of the immunoproteasome subunit β5i in mice and humans. It suppresses the production of pro-inflammatory cytokines and the differentiation of Th1 and Th17 T helper cells while regulatory T cells are promoted and Th2 cells remain unaffected (Kalim et al 2012;Muchamuel et al 2009). In different mouse models, the treatment with ONX0914 suppressed autoimmune disease like rheumatoid arthritis, diabetes (Muchamuel et al 2009), colitis , systemic lupus erythematosus (Ichikawa et al 2012), and experimental autoimmune encephalomyelitis (Basler et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…additional immunological functions. Immunoproteasome deficiency or inhibition affects T cell survival, expansion, and differentiation (Basler et al, 2004;Chen et al, 2001;Kalim et al, 2012;Moebius et al, 2010;Muchamuel et al, 2009;Zaiss et al, 2008), cytokine production (Basler et al, 2011;Basler et al, 2010;Basler et al, 2014;Muchamuel et al, 2009), and progression of autoimmune conditions (Basler et al, 2015). Moreover, mutations in LMP7 and LMP2 in humans cause complex autoimmune and inflammatory phenotypes .…”
Section: Discussionmentioning
confidence: 99%